Literatur und Wahnsinn. Die Kunst der Problemstellung. Issue 4 (7th December 2018) - Schäfer, Armin
Abstract: Literature and Madness. The Art of Posing a Problem . Literary studies and the history of science can collaborate in their ways of posing a problem, which is an art in itself. The article points to a problem that is posed by Marcel Proust's À la recherche du temps perdu . What is the nexus between literature and madness and what makes their difference?